Thyroid hormone-dependent oligodendroglial cell lineage genomic and non-genomic signaling through integrin receptors - Emamnejad, Rahimeh; Dass, Mary; Mahlis, Michael; Bozkurt, Salome; Ye, Sining; Pagnin, Maurice; Theotokis, Paschalis; Grigoriadis, Nikolaos; Petratos, Steven (Frontiers in Pharmacology, 2022)
Multiple Sclerosis (MS) is a heterogeneous autoimmune disease whereby the pathological sequelae evolve from oligodendrocytes (OL) within the central nervous system being targeted by the immune system causing widespread white matter pathology resulting in neuronal dysfunction and neurological impairment. The progression of this disease is facilitated by a failure in remyelination following chronic demyelination. One mediator of remyelination is thyroid hormone (TH) which recently defined its reliance on monocarboxylate transporter 8 (MCT8). MCT8 facilitates the entry of THs into oligodendrocyte progenitor cells/premyelinating oligodendrocytes (OPCs/pre-OLs) to promote differentiation thus promoting remyelination. Patients with MS exhibit downregulated MCT8 near inflammatory lesions, emphasising an inhibition of TH signalling and subsequently its downstream targets such as Akt. However, the role of mammalian target of rapamycin (mTOR) in pre-OLs during neuroinflammation may also be central to the remyelination process governed by various growth promoting signals of which of recent research interest may be dependent on TH-dependent signalling through 1-integrins. The aim of this review is to identify the genomic and non-genomic signalling regulated through mTOR in TH-responsive pre-OLs and mature OLs in mouse models of MS. This review will critique the data that implicate non-genomic Akt and mTOR signalling in response to TH-dependent integrin receptor activation in pre-OLs and whether this can drive remyelination in the context of neuroinflammation and the associated sequelae. Importantly we will outline how novel therapeutic small molecules are being designed to target the integrin receptors on oligodendroglial lineage cells and whether these are viable therapeutic options for future use in clinical trials for multiple sclerosis.